A Case Study of Dynamic Condylar Screw In Cadaver - Dr. Hemant Upadhyay, Dr. Nirav Patel, Dr. Akashdeep A. Meashram (Drugs and Cell Therapies in Hematology, 2021)
A unique surgical variation was noted in upper end of femur bone in 71 years old male cadaver, during a routine dissection class for Post Graduate Students. In this case, the Dynamic Condylar Screw was placed at subtrochanteric region of femur. Knowledge of such surgical variations is important for subtrochanteric fracture of femur bone for orthopedic surgeons and interventional radiologists. It uses in surgeries like subtrochanteric fracture of femur, distal condylar fractures of femur, correction surgery of failed Dynamic Hip Screw, PFN or femur neck surgeries.